COMPETITIVENESS, ENTREPRENEURSHIP, AND ECONOMIC PERFORMANCE: EVIDENCE FROM FACTOR-, EFFICIENCY-, AND INNOVATION-DRIVEN COUNTRIES - Rostami, Nasrin; Mohammadi Khyareh, Mohsen; Mazhari, Reza (Economic Annals, 2019)
Many scholars have highlighted the importance of economic competitiveness for entrepreneurial activity, and hence economic growth. However, few studies quantitatively analyse the interrelationship between competi-tiveness and its role in increasing entrepreneur-ial activity at various stages of development. The aim of this study is to fill this gap in the entrepreneurship literature and to study the causal relationship between the ‘pillars’ of com-petitiveness and the different macroeconomic effects of entrepreneurship, mediated by entre-preneurial behaviour, in a panel of 81 factor-, efficiency-, and innovation-driven countries during 2012–2017. Using a MIMIC model, the results show that innovation, higher education, and technological readiness have a positive and significant impact on the level of entrepreneur-ial activity in the three groups of countries. In addition, development of the financial market and market size has a positive impact on entre-preneurship in factor-driven countries. Higher education and institutional strengthening have a positive and significant impact on the level of entrepreneurship in the efficiency- and innova-tion-driven countries, but are not significant in factor-driven countries. Moreover, the impact of infrastructure on the level of entrepreneurial ac-tivity in the factor-, efficiency-, and innovation-driven countries is positive. Good entrepreneur-ial behaviour generates a simultaneous and/or medium-term favourable effect on the growth of gross domestic product, exports, imports, and employment rate. Therefore, besides immediate growth, it also assures sustainable economic and social progress in the analysed countries. Our results confirm previous findings of empirical studies in the field. These findings are consistent with received economic theory on how national context affects entrepreneurial activity.